Most Radiolucent Lesions of the Jaw Are Classified as Granulomas and Cysts in a US Population - Awad, Manal A. (The journal of evidence-based dental practice, 2013)
Frequency and distribution of radiolucent jaw lesions: a retrospective analysis of 9723 cases. Koivisto T, Bowles WR, Rohrer M. J Endod 2012;38:729-32. Manal A. Awad, BDS, MSc, PhD To determine the frequency, most common sites, and demographic differences in the distribution of radiolucent lesions of the jaw Professional organization Retrospective cohort study Level 2: Limited-quality, patient-oriented evidence Grade C: Consensus, disease-oriented evidence, usual practice, expert opinion, or case series for studies of diagnosis, treatment, prevention, or screening